The Influence of Pshycoeducation Therapy Toward Anxiety Level in Hemodialysis Patients - Zulinda Risma Darmawati; Heru Supriyatno; Dwi Ari Murtiwidigdo (Universitas Padjadjaran, 2021)
Hemodialysis is a treatment used to remove fluid and the waste products from the body when the kidneys are not able to perform its function. Hemodialysis can impact on both physical and psychological dimensions, one of psychological impact is anxiety. Anxiety can be managed by pharmacological and nonpharmacological therapy. One of method to reduce the level of anxiety with nonpharmacological approach is psychoeducation. The study aimed to know differences between anxiety level before and after implementing psychoeducation therapy on hemodialysis patients. This study was type of pre-experimental with one group pre test post test without a control group and involved 30 patients. The technique sample in this study was taken by consecutive sampling. The instrument use questionnaire Hamilton Anxiety Rating Scale (HARS) to determine the level of anxiety before and after a psychoeducation Therapy.Psychoeducation instrument that used is a checklist of activities patient participates in from first session to third session according to standard operating procedures. There was significant difference between the mean level of anxiety on hemodialysis patients before and after psychoeducation is 4.8 (p= 0.000). The study recommended to use a pshycoeducation Therapy to reduce anxiety on hemodialisys patients in early period. Keywords: Hemodialysis, anxiety, psychoeducation.